A COMPARATIVE ANALYSIS OF ACCESS TO SPECIALIZED OUTPATIENT MEDICAL CARE IN BULGARIA AND THE USA - Tihomira Zlatanova; Nikolay Popov; Ralitsa Zlatanova-Velikova (Journal of IMAB)
The patient's access to medical care is a fundamental component of assessing public health systems. We conducted a questionnaire-style survey in Bulgaria and the USA in order to analyze the access to specialized outpatient care and determine whether there are inequities in access present. The questionnaire was anonymous and was distributed in the March 2023 - May 2023 period via the use of the Google Forms online platform among 395 adult citizens of Bulgaria and 387 adult citizens of the USA. The results show that, according to the respondents, there are inequities present in specialized outpatient medical care (SOMC). In Bulgaria, every fifth participant (20.42%) was xamined by a specialist physician one day after acquiring a referral from the GP, and 35.74% waited over a week. In the USA, the largest portion of the respondents (42.64%) were examined by a specialist a month after and 26.43% after 2-3 months. In the context of the COVID-19 pandemic, the largest portion of respondents in Bulgaria (49.87 %) experienced access to specialist becoming harder, while the largest portion of respondents from the USA didn't experience changes in access.